Attribution to Heterogeneous Risk Factors for Breast Cancer Subtypes Based on Hormone Receptor and Human Epidermal Growth Factor 2 Receptor Expression in Korea. Issue 14 (April 2016) - Park, Boyoung; Choi, Ji-Yeob; Sung, Ho Kyung; Ahn, Choonghyun; Hwang, Yunji; Jang, Jieun; Lee, Juyeon; Kim, Heewon; Shin, Hai-Rim; Park, Sohee; Han, Wonshik; Noh, Dong-Young; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: We conducted a heterogeneous risk assessment of breast cancer based on the hormone receptor (HR) and human epidermal growth factor receptor 2 (HER2) calculating the risks and population-based attributable fractions (PAFs) for modifiable and nonmodifiable factors. Using matched case–control study design from the Seoul Breast Cancer Study and the national prevalence of exposure, the risks and PAFs for modifiable and nonmodifiable factors were estimated for total breast cancers and subtypes. The attribution to modifiable factors was different for each subtype (luminal A, PAF = 61.4% [95% confidence interval, CI = 54.3%–69.8%]; luminal B, 21.4% [95% CI = 18.6–24.9%]; HER2-overexpression, 59.4% [95% CI = 47.8%–74.3%], and triple negative tumors [TNs], 27.1% [95% CI = 22.9%–32.4%)], and the attribution to the modifiable factors for the luminal A and HER2-overexpression subtypes was higher than that of the luminal B and TN subtypes ( P heterogeneity ≤ 0.001). The contribution of modifiable reproductive factors to luminal A type in premenopausal women was higher than that of the other subtypes (18.2% for luminal A; 3.1%, 8.1%, and −3.1% for luminal B, HER2-overexpression, and TN subtypes, respectively; P heterogeneity ≤ 0.001). Physical activity had the highest impact preventing 32.6% of luminal A, 14.5% of luminal B, 38.0% of HER2-overexpression, and 26.9% of TN subtypes ( P heterogeneity = 0.014). Total reproductive factors were also heterogeneously attributed to each breast cancer subtype (luminal A, 65.4%; luminal B, 24.1%; HER2-overexpression, 57.9%, and TN subtypes, −3.1%; P heterogeneity ≤ 0.001). Each pathological subtype of breast cancer by HRs and HER2 status may be associated with heterogeneous risk factors and their attributable risk, suggesting a different etiology. The luminal B and TN subtypes seemed to be less preventable despite intervention for alleged risk factors, even though physical activity had a high preventable potential against breast cancer.